Synthesis and characterization of MnO-doped titanium pyrophosphates (Ti1-xMnxP2O7; x = 0–0.2) for intermediate-temperature proton-conducting ceramic-electrolyte fuel cells - Singh B.; Bhardwaj A.; Gautam S.K.; Parkash O.; Kumar D.; Jadhav H.S.; Song S.-J. (My University, 2025)
MnO-doped TiP2O7 (Ti1-xMnxP2O7; x = 0–0.2) were synthesized by digesting oxide precursors with H3PO4 in a two-step synthesis method. Various compositions of Ti1-xMnxP2O7 were characterized by X-ray diffraction (XRD), thermogravimetric analysis/differential scanning calorimetry (TGA/DSC), scanning electron microscopy (SEM), and electrochemical impedance spectroscopy (EIS). XRD of 1050 °C sintered samples showed the formation of (TiO)P2O7 in ≥15 mol% MnO-doped samples. SEM images of 1050 °C sintered Ti1-xMnxP2O7 samples showed that MnO acts as a sintering aid, with the higher amount of MnO leading to a better densification. It was observed that the ionic conductivities of MnO-doped sintered samples were higher than that of undoped TiP2O7 (TiP) sample. The increase in ionic conductivity of MnO-doped TiP2O7 can be attributed to MnO acting as an acceptor dopant, and increased densification of the MnO-doped samples. In unhumidified air, among various MnO-doped samples, Ti0.9Mn0.1P2O7 (TMP10) showed the highest ionic conductivity with a magnitude of 6.29 × 10−8 S cm−1 at 250 °C and 1.33 × 10−5 S cm−1 at 500 °C. Furthermore, the ionic conductivity of TMP10 was higher than that of Ti0.88Mn0.12P2O7 (TMP12), which could be attributed to the formation of defect pairs in TMP12. The ionic conductivity of TMP10 showed >4 orders of magnitude increase in humidified air (pH2O = 0.12 atm) in 100–270 °C range with a maximum of 6.55 × 10−4 S cm−1 at 180 °C. In addition, comparison with the literature data showed that the ionic conductivity of TMP10 was higher than those observed for the high-temperature sintered TiP2O7 samples. © 2017, Springer-Verlag Berlin Heidelberg.